Quality of Academic Services in the Academic Administration Section - Muh. Darwis; St. Aisyah; Haerul Haerul (International Journal of Administration and Education (IJAE), 2024)
Service quality is the key to the success of performance in an organization. This study aims to determine the Quality of Academic Services in the Academic Administration Section of the Postgraduate Program of the State University of Makassar. To achieve this goal, the researcher determined 10 (Ten) informants with the type of research and the approach used was qualitative descriptive. Data collection is used through observation, interview and documentation techniques. The results of the study show that using data analysis techniques consisting of data collection, data reduction, data presentation, and conclusion drawn. The quality of academic services in the Academic Administration Section of the Postgraduate Program of the State University of Makassar, The results of the study show that the quality of academic services in the Academic Administration Section of the Postgraduate Program of the State University of Makassar is not good because it is not in accordance with the number of employees needed in serving the number of students who need services, for example there are 3 employees so that the quality of service is not good. Therefore, judging from several indicators, namely direct evidence is still inadequate, where the capabilities possessed by employees and the condition of facilities and infrastructure are enough to support the provision of services. Reliability shows that it is good enough, this is seen as appropriate in completing documents, providing information to students accurately and reliably. Responsiveness is good, such as providing services quickly, appropriately and responsively in responding to student desires. The guarantee is still not good because there are still students who complain about the behavior of employees in providing services. Empathy is still not good because there are still students who feel that they are treated differently when receiving services